Pengaruh PPKN terhadap Pembentukan Karakter Siswa SD - Alfyanti Alfyanti; Dianrani Anastasia Purba; Ika Novita Padang; Jenni Romayanti Ginting; Onma Nikita Putri Saragi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Adults are hit by a moral crisis, not only at the level of government leaders and bureaucrats, but it has spread to children as well. This can be seen from student brawls, teenage crimes, and so on. This shows that our nation has lost its identity and character. The aim of this research is to find out and prove the influence of civic education (PKn) learning on student character formation. On the other hand, character is the quality of collective national behavior that is uniquely good, which is reflected in the awareness, understanding, feeling, intention and behavior of the nation and state as a result of thought, heart, feeling and initiative of a person or group of people based on the values ​​of Pancasila. , norms, the 1945 Constitution, diversity with the principle of Bhinneka Tunggal Ika, and commitment to the Republic of Indonesia, so that character education needs to be owned and instilled in students. The aim of this research is to find out and prove the influence of civics education (PKn) on the formation of students' character.